CoStorm: a term map system to aid in a collaborative ideation process. Issue 3 (15th October 2018) - Zhang, Chengwei; López-Parra, Marcelo; Chen, Junyu; Tian, Ling
Abstract: The decisions made during the early stages of a design process have a huge impact on a product. Owing to the explosion of preliminary ideas, however, designers easily lose track of important ideas and significant information and end up being buried in a pile of plain words. Failing to locate an idea in the context of idea generation makes it difficult to generate new ideas or take optimized decisions. In this study, the authors propose the term map approach to provide a complete bird's eye view of all ideas, which is a higher-dimension graphical representation that helps in inspiring ideas and making decisions among design team members. A software application named CoStorm is developed. Through the case study of the cash-flattener module, which is a crucial component of an automated teller machine, this method is found to contribute in facilitating the ideation and decision-making progress.